2016
DOI: 10.1186/s12936-016-1494-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and prevalence of malaria parasites among long-tailed macaques (Macaca fascicularis) in regional populations across Southeast Asia

Abstract: Background: Plasmodium knowlesi and Plasmodium cynomolgi are two malaria parasites naturally transmissible between humans and wild macaque through mosquito vectors, while Plasmodium inui can be experimentally transmitted from macaques to humans. One of their major natural hosts, the long-tailed macaque (Macaca fascicularis), is host to two other species of Plasmodium (Plasmodium fieldi and Plasmodium coatneyi) and is widely distributed in Southeast Asia. This study aims to determine the distribution of wild ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 33 publications
5
62
3
Order By: Relevance
“…A complex nature of Plasmodium spp. infections was observed among the wild macaques studied, which is similar to the results of previous studies on wild macaques in Peninsular Malaysia, Malaysian Borneo, Thailand, Singapore, Laos, Cambodia and the Philippines [34,42,43,44,45,46]. The DNA samples were each collected at single time points and the PCR results may not re ect the actual prevalence or the total number of species of Plasmodium present in each host since it has been observed that the parasitaemia of malaria parasites uctuate over time within a host [2].…”
Section: Discussionsupporting
confidence: 90%
“…A complex nature of Plasmodium spp. infections was observed among the wild macaques studied, which is similar to the results of previous studies on wild macaques in Peninsular Malaysia, Malaysian Borneo, Thailand, Singapore, Laos, Cambodia and the Philippines [34,42,43,44,45,46]. The DNA samples were each collected at single time points and the PCR results may not re ect the actual prevalence or the total number of species of Plasmodium present in each host since it has been observed that the parasitaemia of malaria parasites uctuate over time within a host [2].…”
Section: Discussionsupporting
confidence: 90%
“…Because these parasites’ infections in humans are likely to originate from close proximity between humans and wild macaques, a thorough understanding of the distribution of the zoonotic malaria parasite in nature is essential in the control and prevention of malaria disease in countries and regions under high risk. Recent studies have shown that P. cynomolgi is one of the most common malarial parasites among wild cynomolgus macaques and is uniformly and widely distributed throughout cynomolgus macaque populations in Southeast Asia . Infections in experimentally infected rhesus macaques result in much more severe clinical manifestations than in cynomolgus macaques .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that P. cynomolgi is one of the most common malarial parasites among wild cynomolgus macaques and is uniformly and widely distributed throughout cynomolgus macaque populations in Southeast Asia. 38,[42][43][44] Infections in experimentally infected rhesus macaques result in much more severe clinical manifestations than in cynomolgus macaques. 36 Furthermore, previous studies reported a significantly higher count of parasites in rhesus macaques than in cynomolgus macaques within the same duration after infection.…”
Section: Introductionmentioning
confidence: 99%
“…They also revealed that P. knowlesi, previously hypothesized as having been transmitted to humans via anopheline vectors from overlapping macaque populations, was derived from an ancestral malarial parasite that existed before humans came to Southeast Asia. Since then, high prevalence of P. knowlesi has been detected among free-living macaques at vegetation mosaics and forest fragments in other parts of Southeast Asia, including Indonesia, Cambodia, Laos, and Vietnam (Huffman et al 2013b;Zhang et al 2016). Malaria is now widely recognized as being a threat at human-primate interfaces (Singh et al 2004).…”
Section: Parasites At Human-macaque Interfacesmentioning
confidence: 99%